Pemanfaatan media video interaktif dalam pengembangan lebih lanjut hasil belajar siswa pada materi pencemaran alam di sekolah menengah pertama - Rahma Dewi; Maya Ulfah Sutarba; Unidah Unidah; Syifa Ur Rahmi; Yudi Hadiansyah (Universitas Hamzanwadi, 2022)
Learning media is important to support the success of the learning process. It needs different attention and innovation in making learning media, especially on natural pollution materials. This is so that students can understand pollution and what they must do to minimize pollution. In addition, this study aims to determine the improvement of students' understanding of environmental pollution material through interactive video media. The experimental method with a quasi-experimental design will be used in this study. While the research instruments are the pretest and post-test methods. The research was conducted between experimental and control classes, with different learning methods. In the control class, learning activities are conventional, while in experimental classes, learning methods are carried out using interactive media (videos). The results of the study are known to have a significant influence on the application of interactive video media in improving the understanding of students. Influence and Improvement mainly on cognitive learning outcomes. So interactive video media on environmental pollution materials need to be applied by subject teachers so that learning is more effective and easy for students to understand.